2011
DOI: 10.1002/ejoc.201100228
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fulgides and Fluorophore‐Photoswitch Conjugates

Abstract: Various fulgides based on benzofuryl and indolyl core units with versatile functionalities were synthesized. Substitution at the phenylic site shows only small effects on the photochromic properties compared to the parent compounds 30 and 31. Fulgide–dye conjugates were prepared based on anthryl and coumaryl moieties. Fluorophores were introduced to the fulgide via substitution reaction or copper‐catalyzed azide‐alkyne cycloaddition (CuAAC). The synthesized conjugates show weak fluorescence and quenching prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…These include higher thermal stability, longer lifetimes of the photocolored forms and higher yields of the photocoloration reactions and better persistance to photodegradation. It has been shown that annulation of benzene rings to the five-membered rings of pyrryl, thienyl and furanyl fulgides can promote the additional improvement of these properties [10,[18][19][20][21]. In accordance with these data, we have previously synthesized and studied the photochromic properties of 2-benzo[b]thienylfulgides [22].…”
Section: Introductionmentioning
confidence: 76%
“…These include higher thermal stability, longer lifetimes of the photocolored forms and higher yields of the photocoloration reactions and better persistance to photodegradation. It has been shown that annulation of benzene rings to the five-membered rings of pyrryl, thienyl and furanyl fulgides can promote the additional improvement of these properties [10,[18][19][20][21]. In accordance with these data, we have previously synthesized and studied the photochromic properties of 2-benzo[b]thienylfulgides [22].…”
Section: Introductionmentioning
confidence: 76%
“…The synthesis of quinone 11 started with the known benzofuran 8 , readily prepared from benzoquinone in a Nenitzescu type reaction. 33 Methylation gave the known 5-methoxy derivative 9 , nitration of which gave a mixture of the desired 4-nitro compound 10 along with its 6-nitro isomer in excellent overall yield, but in a 1:2 ratio. Although nitrobenzofuran 10 could be isolated, it was more convenient to reduce the mixture of nitro compounds to the corresponding amines, reduce the ketone with sodium borohydride and then oxidize the aniline with Fremy’s salt and purify the desired quinone 11 at the final stage (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…3-Acetyl-5-hydroxy-2-methylbenzofuran 8 33 (1.62 g, 8.5 mmol) in DMF (30 mL) was added to a stirring suspension of potassium hydride (0.61 g, 15.2 mmol) in DMF (50 mL) at 0 °C. The mixture was stirred at room temperature for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…The purity of this compound was confirmed by 1 H NMR spectroscopy and was used as supplied. All other photoswitches were synthesized following published methods; Azo1,[25] CF 3 -fulgide, [39,40] and SP1 [26].…”
Section: Methodsmentioning
confidence: 99%